Investigation of the Vertical Influence of the 11-Year Solar Cycle on Ozone Using SBUV and Antarctic Ground-Based Measurements and CMIP6 Forcing Data - Asen Grytsai; Oleksandr Evtushevsky; Andrew Klekociuk; Gennadi Milinevsky; Yuri Yampolsky; Oksana Ivaniha; Yuke Wang (Atmosphere, 2020)
The 11-year solar activity cycle in the vertical ozone distribution over the Antarctic station Faraday/Vernadsky in the Antarctic Peninsula region (65.25° S, 64.27° W) was analyzed using the Solar Backscatter Ultra Violet (SBUV) radiometer data Version 8.6 Merged Ozone Data Sets (MOD) over the 40-year period 1979–2018. The SBUV MOD ozone profiles are presented as partial column ozone in layers with approximately 3-km altitude increments from the surface to the lower mesosphere (1000–0.1 hPa, or 0–64 km). Periodicities in the ozone time series of the layer data were studied using wavelet transforms. A statistically significant signal with a quasi-11-year period consistent with solar activity forcing was found in the lower–middle stratosphere at 22–31 km in ozone over Faraday/Vernadsky, although signals with similar periods were not significant in the total column measurements made by the Dobson spectrophotometer at the site. For comparison with other latitudinal zones, the relative contribution of the wavelet spectral power of the quasi-11-year periods to the 2–33-year period range on the global scale was estimated. While a significant solar activity signal exists in the tropical lower and upper stratosphere and in the lower mesosphere in SBUV MOD, we did not find evidence of similar signals in the ozone forcing data for the Coupled Model Intercomparison Project Phase 6 (CMIP6). In the extratropical lower–middle stratosphere and lower mesosphere, there is a strong hemispheric asymmetry in solar activity–ozone response, which is dominant in the Southern Hemisphere. In general, the results are consistent with other studies and highlight the sensitivity of ozone in the lower–middle stratosphere over the Antarctic Peninsula region to the 11-year solar cycle.